Depth‐limiting resistant layers restrict dimensions and positions of estuarine channels and bars - Harm Jan Pierik; Jasper R. F. W. Leuven; Freek S. Busschers; Marc P. Hijma; Maarten G. Kleinhans (The Depositional Record, 2023)
Abstract Estuaries comprise channels vital for economic activity and bars as valuable habitats. They are increasingly under human‐induced pressures (e.g. sea‐level rise and dredging), resulting in morphological changes that affect navigability, flood safety and ecology. Antecedent geology may strongly steer how estuary channels will adapt to these pressures, but is surprisingly absent in most models. Here geological data and a unique bathymetry dataset covering 200 years from the Ems‐Dollard estuary (Netherlands/Germany) were used to demonstrate how local resistant layers force the position and dimensions of confluences and bars on the scale of an entire estuary. These layers limit channel depth and consequently cause widening, resulting in mid‐channel bar formation and increased channel curvature. This could lead to unexpected estuary widening and may cause land loss in densely populated areas. With increasing channel volume (as may happen again under future sea‐level rise), resistant layers in the estuary's substrate become more exposed, which enhances their effects. Many systems around the world contain shallow resistant layers that potentially constrain estuary channel dimensions and steer bank erosion. This highlights that resistant layer effects are important to consider as part of mixed depositional processes in coastal environments. It is therefore necessary to globally account for the effects of inherited resistant layers in the possible response of estuaries to sea‐level rise and increased tidal penetration.